Combined GLP-1, oxyntomodulin, and peptide YY improves body weight and glycemia in obesity and prediabetes/type 2 diabetes: a randomized single-blinded placebo controlled study - Behary,P; Tharakan,G; Alexiadou,K; Johnson,N; Wewer,Albrechtsen NJ; Kenkre,J; Cuenco,J; Hope,D; Anyiam,O; Choudhury,S; Alessimii,H; Poddar,A; et al. (Diabetes Care, 2019)
OBJECTIVE: Roux-en-Y gastric bypass (RYGB) augments postprandial secretion of glucagon-like peptide 1 (GLP-1), oxyntomodulin (OXM), and peptide YY (PYY). Subcutaneous infusion of these hormones ("GOP"), mimicking postprandial levels, reduces energy intake. Our objective was to study the effects of GOP on glycemia and body weight when given for 4 weeks to patients with diabetes and obesity. RESEARCH DESIGN AND METHODS: In this single-blinded mechanistic study, obese patients with prediabetes/diabetes were randomized to GOP (n = 15) or saline (n = 11) infusion for 4 weeks. We also studied 21 patients who had undergone RYGB and 22 patients who followed a very low-calorie diet (VLCD) as unblinded comparators. Outcomes measured were 1) body weight, 2) fructosamine levels, 3) glucose and insulin during a mixed meal test (MMT), 4) energy expenditure (EE), 5) energy intake (EI), and 6) mean glucose and measures of glucose variability during continuous glucose monitoring. RESULTS: GOP infusion was well tolerated over the 4-week period. There was a greater weight loss (P = 0.025) with GOP (mean change -4.4 [95% CI -5.3, -3.5] kg) versus saline (-2.5 [-4.1, -0.9] kg). GOP led to a greater improvement (P = 0.0026) in fructosamine (-44.1 [-62.7, -25.5] µmol/L) versus saline (-11.7 [-18.9, -4.5] µmol/L). Despite a smaller weight loss compared with RYGB and VLCD, GOP led to superior glucose tolerance after a mixed-meal stimulus and reduced glycemic variability compared with RYGB and VLCD. CONCLUSIONS: GOP infusion improves glycemia and reduces body weight. It achieves superior glucose tolerance and reduced glucose variability compared with RYGB and VLCD. GOP is a viable alternative for the treatment of diabetes with favorable effects on body weight.